Commanding Right and Forbidding Wrong in Islamic Thought: By Michael Cook (Cambridge, UK: Cambridge University Press, 2000. 702 pages.) (American Journal of Islam and Society, 2003)
This book, an historical survey of the Islamic injunction to command rightand forbid wrong, a biographical exposé of Muslims who understood andpracticed this principle, and a bibliographical reference, is a welcome andtimely addition to the literature on Islamic thought. Detailed and extensive,yet not particularly difficult to read, it is equally accessible to all readers. Itsmain theme is the basic Islamic individual and communal duty to stop otherpeople from doing wrong. Cook contends that few cultures have paid suchmeticulous concern to this matter, despite the issue’s intelligibility in justabout any culture.As a central Islamic tenet, this principle could not be ignored, and yet itssociopolitical implications and consequences made it the focus of rigorousattention by Muslim scholars. The doctrine inexorably brings up the balancingand equally sacrosanct value of privacy, together with issues of knowledge,specialization, competence, and stability – the “how” of the whole matter.After all, the act of forbidding wrong was not supposed to undermine theprinciple by becoming an intrusive breach of privacy, an excursus into socialprying, or a potential justification for unmitigated rebellion against the state.The book consists of five parts comprising 20 chapters. Part I sets thedescriptive framework by elaborating the normative material found in theQur’an, Qur’anic exegesis, tradition, and biographical literature about earlyMuslims. Part II is dedicated to the Hanbali school ince its foundation byAhmad ibn Hanbal (d. 241/855) in Baghdad. The author traces its shiftinginfluences in Damascus and Najd, where the school continues to have a holdin the Saudi state to this day. Part III deals with the Mu‘tazilis and their Zaydiand Imami heirs, all of which, Cook contends, provide the richest documentationfor the intellectual history of forbidding wrong. The remaining Sunnischools of thought, the Khariji Ibadis, together with a chapter on al-Ghazali’stackling of the duty and another chapter pulling together the discussion ofclassical Islam, comprise Part IV. Finally, Part V surveys the duty’s saliencein modern Islamic thought and developments in both the Sunni and Imamischools and engages in a comparative exercise with this duty’s pre-Islamicantecedents and with non-Islamic cultures, including the modern West ...